Protection of Road Safety and Proper Functioning of the Road Haulage Market (Case Study) - Robert Stefanicki (Socialiniai Tyrimai, 2015)
The article is about an important issue of regulating the minimum cost of production and, consequently, prices for the representation of entrepreneurs (associations) with reference to the requirements of road safety. These issues are often the subject of the case law at the Court of Justice at the level of the implementation of the rules governing competition. Recently the question was settled under a preliminary ruling concerned the requirements of Italian law, which, in the name of road safety protection, does not allow to offer prices lower than those benefits rigid minimum rates set by the service provider. The issues that are contrary to a competitive market, price-fixing agreements, are no strangers in different Member States, as exemplified by the findings of the national organization representing independent professionals. The question remains whether those situations are best remedied at the pace of the case law at the Court of Justice or whether there is a need for European Union legislation on the matter in the circumstances where transport contributes to the competitiveness of Europe. There is an interdependence between transport, environment, innovation and social as well as economic policies. The effort invested in this research translated into awareness of the complexity of the subject matter and – the author would encourage – possibilities for further exploration (which would require separate in-depth studies).